Answer:
Inverse of
is
![f^(-1)(x)=√(x+16)](https://img.qammunity.org/2021/formulas/mathematics/high-school/avt7usz4ckya0jbvsz0ashabdjgvgs8px4.png)
Option A is correct option.
Explanation:
We need to find inverse of
![f(x)=x^2-16](https://img.qammunity.org/2021/formulas/mathematics/high-school/1u9fyju1b69szoerwtuaeh8azbu3bidlpa.png)
For finding inverse replace f(x) with y
![y=x^2-16](https://img.qammunity.org/2021/formulas/mathematics/high-school/ain1pbe2afzmj3tjc84069qvrpeuqthmwy.png)
Now, solve for x
Adding 16 on both sides
![y+16=x^2-16+16\\y+16=x^2\\=> x^2=y+16](https://img.qammunity.org/2021/formulas/mathematics/high-school/zfmf6jt901mkuip0yz2b114jo6lph13nk7.png)
Taking square root on both sides:
![x^2=y+16\\√(x^2) =√(y+16) \\x=√(y+16)](https://img.qammunity.org/2021/formulas/mathematics/high-school/9hdqyoaumqmn6odjflp9m5wmj7n84of92a.png)
Now replace x with f^{-1}(x) and y with x
![f^(-1)(x)=√(x+16)](https://img.qammunity.org/2021/formulas/mathematics/high-school/avt7usz4ckya0jbvsz0ashabdjgvgs8px4.png)
So, inverse of
is
![f^(-1)(x)=√(x+16)](https://img.qammunity.org/2021/formulas/mathematics/high-school/avt7usz4ckya0jbvsz0ashabdjgvgs8px4.png)
Option A is correct option.